Migrantes nordestinas e escolarização no Pontal Mineiro (1950 e 1960): desafios, resistências, embates e conquistas - Silveira, Daiane de Lima Soares (2014)
This present dissertation aims to introduce the northeastern migrant women history, by the migration stream occurred from northeastern Brazil to Pontal Mineiro , in the 1950 and 1960 decades. This woman schooling is analyzed by reflexing about the culture relations between the northeastern migrant and local people inside the school; besides, the challenges faced by them for their insertion and endurance into the Ituiutaba and region school institutions also are analyzed. It is questioned the schooling difference between the migrant women and men, which is higher for the women. The modern age conception of migration and schooling are discussed in order to better comprehend the object. The first concept is considered as people transference to one frontier to another, either spontaneously or not, also it is observed the politics, social and cultural questions that can be choice influence or expulsive influence to people. As the schooling, its constitution starts from the civilization project, that had emphasis in the XIX century, in Europe, and that was publicized in Brazil. The timeframe is justified by the migration stream intensity, which is greater in the both decade, when it was expressive economic development in this region due to cereal production raise, especially rice. This situation caused the grain processing industry increase. This was the mainly factor that has stimulated the migration, due to country advertisement by radios, newspapers and magazines. Besides, other migrant also noticed the good news. From the 1970 decade, some reasons such as the agriculture decline, the northeaster traffic prohibition, had caused the migration stream reduction. Using the oral history, 21 interviews has been realized; also the search to that time served newspaper, school proceedings, IBGE data and photographer pictures has been used, with the purpose of proceeding the source crossing. With the bibliographic study we can analyze the collected information. It has been perceived that prejudice and discrimination marked the cultural relations experienced in school spaces, in which migrant women and local people was inserted, because these women mores, way of life, anyway their identity has been taken as different and less considered. Nevertheless this woman did not stay passive in front of this situation, beyond this, they faced this challenge, as many others such as the hard migrant social condition. The migrant women schooling index higher than the migrant men one, have shown itself as one more achievement, because they were able to use mechanisms and tactics in a manly hierarchy society. Such venture is related to the origin local context, in other words, to Rio Grande do Norte and Paraíba states educational history and northeastern man cultural education.